Comparison of surgical dislocation and impacting bone graft and surgical dislocation and rotational osteotomy for the treatment of ARCO III femoral head necrosis. Issue 20 (15th May 2020) - Xia, Tianwei; Liu, Jinzhu; Shi, Le; Zhang, Chao; Yao, Chen; Shen, Jirong
Abstract : Abstract: Hip preserving procedures are still a challenge in late-stage osteonecrosis of femoral head (ONFH) patients. We aimed to compare the clinical outcomes of surgical dislocation and impaction bone graft and surgical dislocation and rotational osteotomy for treatment of ONFH in Association Research Circulation Osseous (ARCO) stage III patients. We retrospectively reviewed 30 ARCO stage III patients (33 hips) who had surgical dislocation and impaction bone graft or surgical dislocation and rotational osteotomy in our center from June 2012 to December 2017. Baseline characteristics, clinical evaluation using Harris score and radiologic evaluation up to 12 months after surgery were recorded and compared. Fifteen patients (17 hips) were in the surgical dislocation and impaction bone graft group and 15 patients (16 hips) were in the surgical dislocation and rotational osteotomy group. No significant differences in age, gender, etiology, ARCO stage, duration of illness, operation time, and length of hospitalization were observed between the 2 groups. Compared to preoperation Harris score, the Harris score of 6 months postoperation and 12 months postoperation significantly improved. At 12 months postoperation, the excellent and good rate was 76.5% in the impaction bone graft group and 87.5% in the rotational osteotomy group. No significant difference in Harris scores was detected in the 2 groups. Surgical dislocation and impaction bone graft and surgical dislocation and rotational osteotomy had satisfactory 1-year efficacy for ARCO III ONFH patients. Surgical dislocation and rotational osteotomy had better short-term efficacy than surgical dislocation and impaction bone graft.